1999
DOI: 10.1128/iai.67.1.302-307.1999
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces boulardii Protease Inhibits the Effects of Clostridium difficile Toxins A and B in Human Colonic Mucosa

Abstract: Saccharomyces boulardii is a nonpathogenic yeast used in the treatment of Clostridium difficile diarrhea and colitis. We have reported that S. boulardii inhibitsC. difficile toxin A enteritis in rats by releasing a 54-kDa protease which digests the toxin A molecule and its brush border membrane (BBM) receptor (I. Castagliuolo, J. T. LaMont, S. T. Nikulasson, and C. Pothoulakis, Infect. Immun. 64:5225–5232, 1996). The aim of this study was to further evaluate the role of S. boulardii protease in preventing C. d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
116
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 332 publications
(122 citation statements)
references
References 36 publications
(66 reference statements)
0
116
0
6
Order By: Relevance
“…Some mechanisms through which S. boulardii make its therapeutic action is by liberating polyamines that stimulate the reparation of intestinal cells and the synthesis of the colonic mucosae, which increase the generation of short-chain fatty acids and enzymes which hydrolyse several disaccharides (lactase, maltase and sucrase or invertase; Profir et al 2015). Saccharomyces boulardii proteases are known to inhibit Toxin A and Toxin B of C. difficile, which are mainly responsible for diarrhoea and colitis (Castagliuolo et al 1999).…”
Section: Probiotics Implications Of S Boulardii In Human Healthmentioning
confidence: 99%
“…Some mechanisms through which S. boulardii make its therapeutic action is by liberating polyamines that stimulate the reparation of intestinal cells and the synthesis of the colonic mucosae, which increase the generation of short-chain fatty acids and enzymes which hydrolyse several disaccharides (lactase, maltase and sucrase or invertase; Profir et al 2015). Saccharomyces boulardii proteases are known to inhibit Toxin A and Toxin B of C. difficile, which are mainly responsible for diarrhoea and colitis (Castagliuolo et al 1999).…”
Section: Probiotics Implications Of S Boulardii In Human Healthmentioning
confidence: 99%
“…34,35 One of the mechanisms, which has been demonstrated in animals, involves the production of a 54 kDa serine protease that inactivates a receptor for toxin A of C. difficile and directly degrades C. difficile toxins A and B. 36 Another mechanism involves secretion of increased levels of secretory immunoglobulin A (IgA) and IgA antitoxin A. 37 Moreover, both in vitro and in vivo studies have shown that S. boulardii exerts its anti-inflammatory activity, in part, by modulating host MAP kinase signalling pathways.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…boulardii was believed to protect animals against Clostridium difficile intestinal disease via degradation of the toxin receptor on the intestinal mucosa. 24 Helicobacter pylori, a major cause of gastric inflammation and ulceration, was reportedly suppressed by strains of L. reuteri that share similar glycolipid specificity, and therefore could inhibit binding of the pathogen to the glycolipid receptors. 25…”
Section: Conventional Use Of Probioticsmentioning
confidence: 99%